ANTIBACTERIAL ACTIVITY OF FERMENTED WHEY BEVERAGE BY PRODUCTS FROM BUFFALO DANGKE - Fatma, -; Malaka, Ratmawati; Hajrawati, -; Taufik, Muhammad (Proceeding Buffalo International Conference, 2013)
Whey derived from by-product processing dangke Buffalo has not been widely utilized in Enrekang. Nutrition components of whey allow to be processed into fermented beverage products. Lactobacillus acidophilus FNCC 0051 is one of the bacteria used for the manufacture of fermented beverage products. The addition of these bacteria can be generated of functional food products. This product can inhibit the growth of pathogenic bacteria (antibacterial). The objectives of the research were to evaluate the antibacterial activity of fermented whey beverage ingredient by-product from Buffalo dangke. The research was conducted according to completely randomized design with a factorial pattern of sucrose level respectively: 0, 9, 12 and 14% as first factors and duration of incubation (4, 8, and 12 hours, respectively) as second factor and 5 replications. Inoculated whey with L. acidophilus then tested with pathogen bacteria (S. aureus FNCC 0047 and E. coli FNCC 0091) to determine the inhibition zone as indicator of antibacterial activity. The results showed that whey fermentation using basic ingredients of buffalo dangke could inhibit the growth of S. aereus or E. coli. Inhibiton zone against pathogenic bacteria significantly enhanced as increasing level of sucrose or incubation time.